Establishment and Validation of Competitive Counterflow as a Method To Detect Substrates of the Organic Anion Transporting Polypeptide 2B1 - Schäfer, Anima M; Bock, Thomas; Meyer Zu Schwabedissen, Henriette E (Molecular pharmaceutics, 2018)
The organic anion transporting polypeptide (OATP) 2B1 is ubiquitously expressed and known to facilitate cellular entry. It is widely accepted that transport proteins play a pivotal role in pharmacokinetics. Consequently, testing for interaction with drug transporters became an important part in the assessment of new molecular entities in order to predict and prevent drug-drug interactions. Recently, competitive counterflow (CCF), an indirect method allowing the identification of substrates, was successfully applied to the organic cation transporter 2. It was the aim of this study to test whether CCF can be used to identify substrates of OATP2B1. A protocol for CCF experiments using estrone 3-sulfate (E S) as the driven compound in expression-verified MDCKII-OATP2B1 cells was established. The protocol was tested using a substance library, which was prior screened for inhibition of OATP2B1-mediated transport accounting for both E S-binding sites. In CCF experiments, all previously reported OATP2B1 substrates significantly reduced the amount of E S in equilibrium, classifying them as substrates. In addition, we identified and verified novel substrates of OATP2B1, namely, astemizole and domperidone. Results of the CCF were complemented with cytotoxicity assays or cell-based reporter gene assays to validate the finding of etoposide and teniposide or hyperforin being substrates of OATP2B1, respectively. Our study indicates that the method of CCF can be used to identify substrates of OATP2B1, irrespective, whether interacting with binding site A or A and B, but is limited by solubility issues or the amount of transporter that is expressed in the used cellular system.